PPP Method with Kalman Filter for Detection of Shifting GNSS Observation Points due to the Palu 2018 Earthquake - Handoko, Dadang; Widjajanti, Nurrohmat; Muslim, Buldan (2019)
Precise Point Positioning (PPP) method is one of the absolute positioning methods using precision orbital data based on GNSS satellites which is currently developing rapidly as the position accuracy is generated. The PPP method uses a carrier wave phase data or pseudorange from the observation of a geodetic type GNSS receiver that is combined with other measurement error corrections. To produce accuracy with the centimeter-level in static measurements. The earthquake that occurred on September 28, 2018, with a magnitude of 7.4 MW, centered on 26 km North of Doggala Central Sulawesi caused a strong shock and produced a tsunami that hit the city of Palu. In this study, the shift detection of GNSS observation points using RINEX data from dual-frequency observations from CORS CTOL, CMAK, CBAL, CPAL, CAMP, CMLI and CRAU stations. Data were processed with the GoGPS software PPP method with 1st order ionospheric correction, Ocean tide loading, tropospheric correction, orbit and precision satellite clock, PCV correction, DCB correction (P1P2 and P1C1). The results of this study The overall standard deviation value of the smallest CORS station at the CBAL station coordinates is 4.786 mm for the East component, 1.794 mm for the North component and 7.595 mm for the Up component. The convergence time needed to achieve accuracy with a level of 5 mm is reaching 4 hours. Visualization from the trend of coordinate each epoch shows that there are significant variations in the detection of earthquakes in the East and North components of the CMAK, CMLI, and CPAL stations.